Web-Based Library Information System at Santo Yospeh High School Medan - Ijonris, Yusuf (Yayasan Kita Menulis, 2024)
The library is very important in supporting the knowledge and information of students in schools because the library is part of the learning resources that schools must have, therefore the library is often referred to as the heart of education. Currently, the Library of Santo Yospeh High School Medan, which currently has not been computerized, makes it difficult to carry out the process of borrowing and returning books, as well as registering as members and giving fines. For this reason, SMA Santo Yoseph Medan requires a library that has a web-based library system. The tools used to design this library information system are by using the PHP and MySql programming languages. The results of the design of this web-based library information system are expected to be able to help library admins in carrying out the process of borrowing and returning books, processing book and member data, and creating library data reports